If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + -1X + 1 + -1(4 + -1) = -2 + -1X(4) Combine like terms: 4 + -1 = 3 -4 + -1X + 1 + -1(3) = -2 + -1X(4) Multiply -1 * 3 -4 + -1X + 1 + -3 = -2 + -1X(4) Reorder the terms: -4 + 1 + -3 + -1X = -2 + -1X(4) Combine like terms: -4 + 1 = -3 -3 + -3 + -1X = -2 + -1X(4) Combine like terms: -3 + -3 = -6 -6 + -1X = -2 + -1X(4) Reorder the terms for easier multiplication: -6 + -1X = -2 + -1 * 4X Multiply -1 * 4 -6 + -1X = -2 + -4X Solving -6 + -1X = -2 + -4X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '4X' to each side of the equation. -6 + -1X + 4X = -2 + -4X + 4X Combine like terms: -1X + 4X = 3X -6 + 3X = -2 + -4X + 4X Combine like terms: -4X + 4X = 0 -6 + 3X = -2 + 0 -6 + 3X = -2 Add '6' to each side of the equation. -6 + 6 + 3X = -2 + 6 Combine like terms: -6 + 6 = 0 0 + 3X = -2 + 6 3X = -2 + 6 Combine like terms: -2 + 6 = 4 3X = 4 Divide each side by '3'. X = 1.333333333 Simplifying X = 1.333333333
| 9=-2+y | | (6p+5)=18+15 | | 4(m-5)=2(m+3)+4 | | 3n+5-2n=-2 | | -8n=-40 | | 3t^2-16t+26=0 | | 6/5(5k+2)=-36 | | 2x+40(5x)=360 | | 2(x+8)=14x | | -6(1+4n)=-6n+6(n-9) | | h(-4)=7-2(-4) | | 4x+17=180 | | d/3.2=48 | | 2x-20i=8-4yi | | 5(2q+4)=2(4q-6) | | -6x+30=3(x-5) | | g(-4)=5(-4) | | 345=562.5-7.5x | | 4x(7)=70 | | 6/5(5k+2)=36 | | 4x-17+(3x+11)=180 | | 3+x/2=7 | | Y=-0.1x^2+6x+120 | | 4b+16+3b=46 | | pr=qs | | -21x^2+44x-15= | | 3x+5y-2z=22 | | 2(3m-4)=5(m+7) | | 12=10c | | 4b+16+2b=4b | | 6(0)+3X^2=2 | | 2(5+4n)=10(1-9n)+7n |